2004
DOI: 10.1007/s00464-004-8101-0
|View full text |Cite
|
Sign up to set email alerts
|

The long-term follow-up of patients with positive intraoperative cholangiograms during laparoscopic cholecystectomy

Abstract: LCBDE is safe and effective in the majority of cases when an attempt at transcystic LCBDE was made. In addition, after long-term follow-up of >5 years, the outcomes were similar if the stones were removed by intraoperative laparoscopic methods versus postoperative ERCP. LCBDE seems worthy of pursuing when an intraoperative CBD stone is discovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…Laparoscopic CBD exploration (LCBDE) was advocated by 61% of surgeons, whereas 25% recommended post‐operative ERCP. In the same paper, LCBDE was found to have similar long term outcomes to post‐operative ERCP . The use of a flexible choledochoscope and wire basket for laparoscopic transcystic stone removal has been described .…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Laparoscopic CBD exploration (LCBDE) was advocated by 61% of surgeons, whereas 25% recommended post‐operative ERCP. In the same paper, LCBDE was found to have similar long term outcomes to post‐operative ERCP . The use of a flexible choledochoscope and wire basket for laparoscopic transcystic stone removal has been described .…”
Section: Discussionmentioning
confidence: 84%
“…Achieving the ‘critical view of safety’ via dissection of Calot's triangle and IOC have both been advocated as gold standard for preventing BDI in LC . Routine IOC was found to reduce the incidence of BDI by up to 50–70% . For example, one retrospective audit describes IOC highlighting the misinterpretation of the CBD as the cystic duct.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent published series reported a 71% clearance rate with transcystic exploration and without the use of a choledochoscope. The same report also concluded that long-term outcomes after laparoscopic ductal clearance are similar to those for ERCP clearance [25].…”
Section: Discussionmentioning
confidence: 77%
“…
We read with interest the article by Wagner et al [3]. The authors successfully highlighted that simple transcystic maneuvers may clear common bile duct (CBD) stones in 71% of cases with a positive intraoperative cholangiogram that would otherwise have a postoperative endoscopic retrograde cholangiopancreatography (ERCP).
…”
mentioning
confidence: 93%